2020
DOI: 10.1016/j.jadohealth.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Social (Un)distancing: Teammate Interactions, Athletic Identity, and Mental Health of Student-Athletes During the COVID-19 Pandemic

Abstract: Purpose Physical distancing measures to combat the spread of the novel coronavirus have presented challenges for the mental health and well-being of college students. As campus activities ceased, student-athletes abruptly became isolated from teammates and were no longer able to participate in sport activities that are often central to their identity as an athlete. However, student-athletes who have supportive social connections with teammates during this pandemic may maintain their athletic ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
187
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(208 citation statements)
references
References 52 publications
12
187
2
7
Order By: Relevance
“…However, the minority that did was affected by gambling problems and reported an increase in alcohol consumption. The toll of NPIs on sport activities has been quite significant for elite athletes [242] , [243] . Level of stress and anxiety have been observed, especially among women, and linked to worries about the future of the sport.…”
Section: Surveysmentioning
confidence: 99%
“…However, the minority that did was affected by gambling problems and reported an increase in alcohol consumption. The toll of NPIs on sport activities has been quite significant for elite athletes [242] , [243] . Level of stress and anxiety have been observed, especially among women, and linked to worries about the future of the sport.…”
Section: Surveysmentioning
confidence: 99%
“…Research addressing the impact of this pandemic in sports identified specific challenges for athletes’ mental health during the lockdown, such as the difficulty in keeping training conditions ( Pillay et al, 2020 ), the social distancing from teammates ( Graupensperger et al, 2020 ), and the uncertainty regarding the delay or cancelation of future competitions ( Samuel et al, 2020 ). Despite most of these challenges are common for athletes of all ages and levels, research has mainly focused on high performance, professional, and/or Olympic/Paralympic athletes (see also Schinke et al, 2020a , b ; Stambulova et al, 2020 ), letting youth sports’ reality underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies provided important information about the negative effects of detraining periods on performance parameters [10][11][12][13][14][15][16][17]. For example, Morais et al [19] investigated the effect of an 11-week detraining period on some athletic performance components of swimmers and they found impaired performance.…”
Section: Discussionmentioning
confidence: 99%
“…-Indirect effects indicated that student-athletes' change in athletic identity mediated the effects of teammate social support on psychological well-being and depression symptoms [16].…”
mentioning
confidence: 99%